2019
DOI: 10.2298/pif1904211p
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pectobacterium carotovorum subsp. carotovorum isolates from a recent outbreak on cabbage in Bosnia and Herzegovina

Abstract: The causal agent of soft rot disease associated with a cabbage outbreak in Semberija region, Bosnia and Herzegovina, in 2018 was identified and characterized. Symptoms appeared in the form of water-soaked lesions on leaves and specific odour. Disease incidence ranged from 20% to 30%. The causal pathogen was isolated on nutrient agar (NA), King?s B and crystal violet pectate (CVP) media. Eight creamy-white, round and convex bacterial isolates, which produced characteristic pits on CVP medium w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…However, the extent of yield loss is influenced by pathogen−host specificity, as well as numerous external factors (temperature, humidity, etc.) [ 8 ]. Although bacterial soft rot is a disease that affects only agricultural and horticultural crops, the presence of the soft rot-causing Pectobacteriaceae is not only limited to host plants but extends to the weed species growing near the infected fields, as well as water, air, and soil, thus serving as a potent source of inoculum [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the extent of yield loss is influenced by pathogen−host specificity, as well as numerous external factors (temperature, humidity, etc.) [ 8 ]. Although bacterial soft rot is a disease that affects only agricultural and horticultural crops, the presence of the soft rot-causing Pectobacteriaceae is not only limited to host plants but extends to the weed species growing near the infected fields, as well as water, air, and soil, thus serving as a potent source of inoculum [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CEO is known to be effective against soft rot bacteria [36][37][38], as well as in general against both Gram-positive and Gram-negative bacteria [57]. We found that MIC (or minimum bactericidal concentrations, MBC) of CEO was 1% concentration in controlling soft rot pathogens.…”
Section: Discussionmentioning
confidence: 86%
“…All strains belong to the laboratory collection of the Institute for Plant Protection and Environment, and were originated from cabbage in case of P. carotovorum subsp. carotovorum strain Pcc10 [38], and potato in case of strains of P. carotovorum subsp. brasiliensis Pcb62 and D. dianthicola Dd31 [39].…”
Section: Activity On Soft Rot Pathogensmentioning
confidence: 99%
See 2 more Smart Citations